Mapping settlement typologies and business functions in yogyakarta riverbank area - Amijaya, Sita Yuliastuti; Dewangga, Yordan Kristanto (Universitas Gadjah Mada, 2024)
A residential property functions as a place to live. In some conditions, a residential space can be transformed into a business or production space simultaneously. Business or production spaces require indoor comfort, such as the minimum standards for indoor lighting, which can be challenging to achieve in a dense residential area. This affects the typology of business space, which is integrated with the residential function. This research is part of a study of visual comfort or lighting in workspaces or business spaces. This research aims to identify types of dwellings that have changed from residential to business functions in dense settlements such as urban kampungs or villages. The study is in the Suryatmajan subdistrict in Yogyakarta City, including the urban villages of Ledok Macanan, Gemblakan Atas, Gemblakan Bawah, and Cokrodirjan. The identification will produce mapping that provides information regarding the types of residences and businesses found at the study location. The method used is a descriptive-qualitative study, which collects data through field observations, redraws from observations, and short interviews with residents of the study location. The study found six typologies of residential and business space commonly found in the four urban villages in Yogyakarta..